(untitled) (Research, Society and Development, 2022)
The present study arose from the concern about what would be the basic steps or steps to be taught to physical education (PE) teachers so that visual pedagogy can be understood as a socialization strategy between deaf students and listeners. This article aims to describe and analyze which strategies the PE teacher can use to contemplate and include deaf students in regular classrooms, especially in Early Childhood Education. For this, we start from some reflections on approaches in teaching to the deaf, the specificity of Libras as a visual gesture language, the deaf didactics and the rights of children and the deaf throughout history. We approach the PE and the importance of the contents worked on the sung toys and symbolic games. We analyzed the contribution of playful activities developed in the PE classes for the global development of deaf children. We identified the necessary steps to adapt materials and activities in the classes using a visual pedagogy as methodology. This research resulted in the construction of a booklet, with strategies that propose the performance of these activities. We conclude that the Education of the Deaf permeates the bases of Bilingual Education. When adapting activities for deaf students, sign language should be present, being supported by the use of images and based on visual pedagogy. By teaching a new game, rules, conducts, new concepts and terminologies are taught and, stimulating expression by the individual, enabling the integral development of the deaf student.